Elder Crimes of the Law Abiding: Backwards Dresses, Covered Up Messes, and Nursing Homes - Jason S. Ulsperger; Kristen Ulsperger; J. David Knottnerus (Randwick International of Social Science Journal, 2023)
This article uses data from 75 biographies, autobiographies, and research monographs on nursing homes to explore physical neglect and abuse. Linked to crimes of the law abiding concepts, it implies employees see maltreatment as “normal.” It extends lines of research examining bureaucratic forces and their influence on nursing homes. It also provides a history of elder care in the UK and US and a review of structural ritualization theory. Findings concentrate on how rituals involving hierarchical structure, work efficiency, documentation, and rules adversely influence care homes. This includes physical maltreatment involving employee neglect of personal needs of residents, failing to provide medical help, bodily harm, and not maintaining quality living spaces.